Event correlation, extra information and merged policies approaches for integrating intrusion detection and access control systems. - Halboob, Waleed; Alghathbar, Khaled S.; Mamat, Ali; Mahmod, Ramlan; Shamsuddin, Solahuddin (International Information Institute, 2013)
Computer security aims to provide data with three security services namely confidentiality, integrity and availability to protect the data from unauthorized access (or use), unauthorized modification and denial of access, respectively. Access control and intrusion detection systems are used in isolation while the range of their accuracy can be increased if they are integrated. This survey investigates the connection between the intrusion detection and access control systems and then it reviews the existing approaches for integrating them. We determined which intrusion detection types and detection methods are more appropriate to be integrated with access control systems and in which manner.